Illustrated textbook of paediatrics - Lissauer, Tom; Carol, Will (Elsevier, 2022)
This sixth edition of the acclaimed and award-winning 'Sunflower book' comprehensively covers the undergraduate curriculum in paediatrics and child health. Topics are made accessible with numerous colour images, diagrams and case studies, and revision is facilitated by key points and summary boxes. This has made the book a firm favourite of medical students as well as trainees approaching clinical speciality exams, both in the UK and internationally.